(untitled) (Swiss Medical Weekly, 2021)
AIM OF THE STUDY To compare admission characteristics, predictors and outcomes of patients with confirmed coronavirus disease 2019 (COVID-19) hospitalised in a tertiary care hospital in Switzerland during the first and second waves of the pandemic. METHODS This retrospective observational analysis included adult patients with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection confirmed by a real-time reverse transcriptase polymerase chain reaction (RT-PCR) or rapid antigen test and hospitalised at the Cantonal Hospital Aarau from 26 February to 30 April 2020 (first wave) and from 1 October to 31 December 2020 (second wave). The primary endpoint was all-cause in-hospital mortality. The secondary endpoints were transfer to the intensive care unit (ICU) and length of hospital stay (LOS). RESULTS Overall, 486 patients (mean age 65.9 years ± 14.7 SD, 65% male) were included. Ninety-two patients (19%) died during the hospital stay and 92 patients (19%) were transferred to the ICU. Admission characteristics, including comorbidities and frailty, were similar for patients of the first (n = 100) and second wave (n = 386). However, during the second wave the median time from symptom onset to presentation to the emergency department (ED) was shorter (7 days, interquartile range [IQR] 4–9 vs 8 days, IQR 4–11; p = 0.02). In the second wave, most patients received high-dose glucocorticoid treatment (0% vs 76%, p <0.01). In-hospital mortality was similar among COVID-19 patients in the first (19/100, 19%) and second wave (73/386, 19%); this finding persisted after full adjustment in multiple regression models (adjusted odds ratio [aOR] 1.18, 95% confidence interval [CI] 0.49–2.80; p = 0.71). Risk for ICU admission was also similar (24% vs 18%; aOR 0.98, 95% CI 0.46–2.06; p = 0.95). More patients were transferred to rehabilitation facilities in the second wave (18% vs 31%; aOR 2.06, 95% CI 1.04–4.07; p = 0.04) and LOS was 2.5 days shorter (9.0 vs 6.5 days; adjusted difference −2.53 days, 95%-CI −4.51 to −0.54; p = 0.01). Main predictors for in-hospital death were patient age (aOR 1.07, 95% CI 1.02–1.11; p <0.01), male sex (aOR 2.41, 95% CI 1.05–5.55; p = 0.04) and the age-adjusted Charlson comorbidity index (aOR 1.27, 95% CI 1.09–1.48 p <0.01). CONCLUSION Despite differing treatment regimens, mortality and ICU admission remained largely unchanged for COVID-19 patients admitted during the second wave of the pandemic in our tertiary care hospital. However, discharge processes were optimised with patients leaving the hospital earlier and going to rehabilitation facilities more often.